2021
DOI: 10.1016/j.mayocp.2020.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Using Reticulocyte Hemoglobin Equivalent as a Marker for Iron Deficiency and Responsiveness to Iron Therapy

Abstract: Objective: To assess the accuracy of a simplified approach for the diagnosis of iron deficiency anemia (IDA) based on the complete blood cell count (CBC) and reticulocyte analysis. Patients and Methods: Five hundred fifty-six consecutive, nonselected patients referred for diagnosis and/or treatment of anemia were included in this diagnostic study to compare the performance of reticulocyte hemoglobin equivalent (RET-He) versus traditional biochemical markers for diagnosis and treatment of IDA. Complete blood co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
2
11
0
2
Order By: Relevance
“…On the other hand, the main disadvantage of this indicator is that two blood specimens are required to assess the change in RET-He over 1 week. Conversely, baseline RET-He alone was not a strong predictor of haemoglobin response, which has also been previously confirmed in a study of individuals receiving intravenous iron (rather than oral iron) 7…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…On the other hand, the main disadvantage of this indicator is that two blood specimens are required to assess the change in RET-He over 1 week. Conversely, baseline RET-He alone was not a strong predictor of haemoglobin response, which has also been previously confirmed in a study of individuals receiving intravenous iron (rather than oral iron) 7…”
Section: Discussionsupporting
confidence: 67%
“…Strengths of this study include that the analyses were based on a robust randomised controlled clinical trial that used a standard dose of iron (60 mg elemental iron) to elicit a haemoglobin response after 12 weeks of supplementation, a duration of supplementation commonly proposed in WHO guidelines for treatment and prevention of iron deficiency in women 16. One-week change in RET-He was assessed as the reticulocyte index that is optimal for assessing the early responsiveness to iron therapy 7. We used a threshold of 10 g/L to define a haemoglobin response after 12 weeks of iron supplementation as this is what has been suggested globally13; however, we acknowledge that smaller increases may also be clinically meaningful and more women would have elicited a haemoglobin response if a lower threshold was chosen, which may have influenced our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) Related studies have demonstrated the applications of Ret-He in IDA and various clinical settings. (10)(11)(12)(13)(14)(15)(16) Notably, Ret-He provided speedy results to indicate iron status and was not affected by other chronic diseases. Therefore, Ret-He is convenient in the diagnosis and follow-up treatment of IDA among infants, pregnant women, and patients with chronic renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…Սովորաբար երկաթը նշանակվում է մինչև ֆերիտինի և տրանսֆերինի հագեցվածության ցուցանիշների նորմալացումը: Որոշ պացիենտներ (օրինակ` ստամոքսաղիքային տելեանգիէկտազիաներից պարբերաբար արյունահոսող) կարող են ունենալ միջինից բարձր երկաթի պաշարների կարիք: Այն դեպքերում, երբ ֆերիտինի և տրանսֆերինի հագեցվածության ցուցանիշները հակասում են միմյանց, առավելությունը պետք է տալ տրանսֆերինի հագեցվածությանը, քանի որ ֆերիտինը, լինելով սուր փուլի սպիտակուց, մեծապես կախված է զուգորդող քրոնիկական հիվանդությունների առկայությունից: Մոնիթորինգի և երկաթի նկատմամբ պատասխանի գնահատման համար կարևոր ցուցանիշ է նաև ռետիկուլոցիտար հոմոգլոբինը (CHr), որի նշանակությունը դեռևս հետազոտման փուլում է [11]:…”
unclassified